2011
DOI: 10.1021/np200241c
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Biological Evaluation of Jatrophane Diterpenoids from Euphorbia dendroides

Abstract: From the Montenegrin spurge Euphorbia dendroides, seven new diterpenoids [jatrophanes (1-6) and a tigliane (7)] were isolated and their structures elucidated by spectroscopic techniques. The biological activity of the new compounds was studied against four human cancer cell lines. The most effective jatrophane-type compound (2) and its structurally closely related derivative (1) were evaluated for their interactions with paclitaxel and doxorubicin using a multi-drug-resistant cancer cell line. Both compounds e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 22 publications
1
40
0
Order By: Relevance
“…Colorectal carcinoma cell lines (DLD1 and DLD1-TxR), as well as the glioma cell lines (U87 and U87-TxR), showed considerably lower sensitivity to the two jatrophanes. These results recapitulated those obtained in the previous study (Aljancic et al 2011) and indicated the potential of Euph H (225) and Euph S (236) for NSCLC treatment. 225 significantly sensitized NCI-H460/R and DLD1-TxR cells to Paclitaxel (PTX), similar to paclitaxel, R ± verapamil (Dex-VER), and tariquidar (TQ); while 236 demonstrated the moderate chemo-sensitizing effect.…”
Section: Mdr Reversing Activitysupporting
confidence: 90%
See 2 more Smart Citations
“…Colorectal carcinoma cell lines (DLD1 and DLD1-TxR), as well as the glioma cell lines (U87 and U87-TxR), showed considerably lower sensitivity to the two jatrophanes. These results recapitulated those obtained in the previous study (Aljancic et al 2011) and indicated the potential of Euph H (225) and Euph S (236) for NSCLC treatment. 225 significantly sensitized NCI-H460/R and DLD1-TxR cells to Paclitaxel (PTX), similar to paclitaxel, R ± verapamil (Dex-VER), and tariquidar (TQ); while 236 demonstrated the moderate chemo-sensitizing effect.…”
Section: Mdr Reversing Activitysupporting
confidence: 90%
“…Both jatrophanes at 5 lM decreased the IC 50 values of doxorubicin significantly, showing a similar reversal potential to 'verapamil'. These results pointed to the potential of 396 and 397 to reverse paclitaxel and doxorubicin resistance in the MDR cancer cell line used (Aljancic et al 2011). Valente et al (2012) isolated three new jatrophanes euphomelliferine (293), euphomelliferenes A (294) and B (295) along with two known jatrophanes 306 and 302 from E. mellifera.…”
Section: Mdr Reversing Activitymentioning
confidence: 91%
See 1 more Smart Citation
“…30,31 Compounds that stabilize MT represent potential therapeutic approach for the treatment of Alzheimer's disease and related tauopathies. 32 In this study 16 jatrophane diterpenoids isolated from Euphorbia dendroides 33,34 and latex extracts from E. dendroides and Euphorbia nicaeensis induced decrease in the frequency of MN and manifested protective effect on human lymphocytes DNA. Table 1.…”
mentioning
confidence: 75%
“…Previous studies showed increasing application of herbal formulations for cardiovascular disease [1][2][3][4][5][6][7]. These formulations are made up of different herbs and extraction of herbal ingredients is conducted in boiling water.…”
Section: Introductionmentioning
confidence: 99%